2009
DOI: 10.1002/dvdy.22007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of dystrophin and the microtubule‐binding protein ELP‐1 causes progressive paralysis and death of adult C. elegans

Abstract: EMAP-like proteins (ELPs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…Additionally, we also showed that dys-1(cx18) display temperature sensitivity in their thrashing movement. Similar movement data for dys-1(cx18) were reported at 25°C (Hueston and Suprenant, 2009); thus, our data are consistent with published data. The nonsense mutation in dys-1(cx18) corresponds to termination at AA 2721, which is immediately before the start of spectrin repeat domain 5, which starts at AA 2725.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we also showed that dys-1(cx18) display temperature sensitivity in their thrashing movement. Similar movement data for dys-1(cx18) were reported at 25°C (Hueston and Suprenant, 2009); thus, our data are consistent with published data. The nonsense mutation in dys-1(cx18) corresponds to termination at AA 2721, which is immediately before the start of spectrin repeat domain 5, which starts at AA 2725.…”
Section: Discussionsupporting
confidence: 93%
“…Given that strength and thrashing ability are not compromised to the same extent in dys-1(cx18) as in dys-1(eg33) , we wanted to further investigate the differences between the two strains. Upon reviewing the published literature on dys-1(cx18) , we found that Hueston and Suprenant (2009) had previously observed worse locomotion at 25°C than at 20°C, which would be consistent with cx18 being a temperature-sensitive allele. We confirmed that dys-1(cx18) , but not dys-1(eg33) , displays temperature sensitivity in the extent of thrashing ability (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As indicated in Figure 2 , UNC-52 (perlecan), integrins (PAT-2/PAT-3), and the four-protein complex are found at the base of both M-lines and dense bodies. At the dense bodies, there are additional dense body-specific proteins such as DEB-1 (vinculin) [ 9 ], ATN-1 ( α -actinin) [ 27 ], UIG-1 (Cdc42 GEF) [ 28 ], ALP-1 (ALP/Enigma) [ 29 ], DYC-1 [ 30 ], and ELP-1 (EMAP-like protein) [ 31 ]. The only known nematode M-line-specific protein is UNC-89 (obscurin) [ 32 , 33 ]; as mentioned below, UNC-98 and UNC-96 are most prominent at M-lines.…”
Section: Discovery Of Muscle Attachment Components Through Immunolmentioning
confidence: 99%
“…␣ -Dystroglycan, localized extracellularly, is heavily glycosylated and binds to laminin and perlecan in the BM and ␤ -dystroglycan in the basal membrane [Hemler, 1999;Henry and Campbell, 1999;Barresi and Campbell, 2006]. ␤ -Dystroglycan, through the dystrophin-glycoprotein complex, has been reported to interact intracellularly with both actin filaments and microtubules [Campbell, 1995;Henry and Campbell, 1999;Barresi and Campbell, 2006;Ayalon et al, 2008;Cerecedo et al, 2008;Bozzi et al, 2009;Hueston and Suprenant, 2009;Prins et al, 2009]. DAG1-null mice were embryonic lethal due to a poor assembly of Reichert's membrane, in addition to gastrulation and mesoderm formation defects [Williamson et al, 1997].…”
mentioning
confidence: 99%